Urgensi Micro Business Game dalam Meningkatkan Manajemen Bisnis dan Pengetahuan Literasi Keuangan - Sulaiman Helmi; Ulfa Kurniasih; Afina Aninnas (Velocity: Journal of Sharia Finance and Banking, 2022)
The Micro, Small, and Medium Enterprise sector is one of the factors driving the trend of economic growth in indonesia. In order to support the government’s efforts in advancing SMEs, Jateng Bank as one of the institutions in collaboration with the German SBFIC (Saving Banks Foundation for International Cooperation) participated in thes efforts by holding MBG (micro business game training). This article aims to describe the urgency of MBG training for the Micro, Small, and Medium Enterprise actors or prospective actors in improving business management knowledge and financial literacy. This study uses a qualitative method, namely by collecting primary data sources trough interviews with the trainer of MBG Jateng Bank and also collecting data sources from literature review trough previous research literatures. The result of this research is that MBG training has a very important role in improving business management and financial literacy, especially in increasing the effectiveness and efficiency of Micro, Small, and Medium Enterprises.